THE ROLE OF KUA IN THE IMPLEMENTATION OF ISLAMIC LAW IN INDONESIA - Saepudin, A (Inovasi: Jurnal Diklat Keagamaan, 2016)
Islamic law is the regulation implemented in Indonesia which isabsorbed from product of law as stated in the various books of fiqhwhich has been written by the ulama such as about marriage,inheritance, zakat, wakaf and Hajj. To implement Islamic law inIndonesia, it needs presence for structure in the form of a legitimateinstitution. KUA is a government agency that has a role and duty tocarry out the partially affairs of Islam religion in Indonesia.